Prospective evaluation of socket shield technique for immediate implant placement in anterior maxilla - Bhagol Amrish; Ashwin V.; Singh Virendra (EDP Sciences, 2022)
Purpose: The purpose of the study was to report the four year implant survival rate for immediate implant placement using socket shield technique. Objectives included evaluation of the esthetic outcomes and to report any complications associated with this technique. Material and methods: This study is a prospective cohort of 10 consecutive patients with Implant placement between the maxillary first premolars using socket shield technique. Data were collected (PPD, BOP, PES, buccal width of keratinized mucosa, peri-apical radiographs and photographs) to assess and compare the changes in peri-implant tissues in pre-operative and follow up visits. Results: All the implants osseointegrated successfully without any adverse events. Peri-implant probing revealed healthy conditions in terms of pocket depth and bleeding on probing. Mean buccal width of keratinized mucosa of 4.1 was achieved. A mean pink aesthetic score of 12.3 was recorded. Conclusion: Within the limitations of this study, the results were suggesting that socket shield technique is effective in maintaining the hard and soft tissue architecture of anterior maxillary region and delivers high esthetic outcomes with shorter duration of treatment period. However, a prospective randomized study to compare socket shield with other techniques is needed to draw any definitive conclusion.